Development of Microsoft Sway-Based Learning Media for Kindergarten Students - Dya Nurli Herliza; Evi Selva Nirwana (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning media is growing along with the times. However, many teachers are still developing media that do not keep up with the times and do not use technology as material delivery. This type of research is RD with the ADDIE research model. This study aims to develop Microsoft Sway learning media for children aged 5-6 years with the sub-theme of Natural Symptoms. The results of learning media research developed using Microsoft Sway are categorized as valid with a media expert percentage of 89.7% and material experts 68.7%. The media is said to be practical by obtaining a score of 88.3% from the teacher's response questionnaire. The conclusions of this study are the application of Microsoft Sway media development to group B students at kindergarten fosters children's learning motivation. Children's learning outcomes increase with the presence of Microsoft Sway media. With Microsoft Sway media, children pay more attention to the teacher when delivering material.